Stohastični abakus - Houška, Luka (Matrika, 2024)
The article presents stochastic abacus in detail, how the algorithm works and why it works. Using the stochastic abacus, pass-the-buck games are analyzed on various graphs, revealing a natural connection with the Fibonacci numbers.
Keywords: algorithms; algoritmi; Engelov stohastični abakus; Fibonacci numbers; Fibonaccijeva števila; game theory; graph theory; pass-the-buck games; podajanje evra; stochastic abacus; teorija grafov; teorija iger